A Paraneoplastic Optic Neuropathy Revealing a Pulmonary Epidermal Carcinoma - Yassine Mouzari; Issam Fiqhi; Belfaiza Soukaina; Taoufiq Abdellaoui; Mohammed Allaoui; Karim Reda; Abdel Bar Oubaaz (Indian Journal of Medical Specialities)
Paraneoplastic optic neuropathy is a relatively rare ocular manifestation. We report the case of a patient with bilateral papilledema revealing a pulmonary squamous cell carcinoma. Paraneoplastic neuropathy is linked to an immune reaction by the presence of autoantibodies against collapsin responsive mediator protein 5 . Diagnosis is based on the determination of these autoantibodies and the search for occult cancer by PET scan. Treatment is often based on corticosteroid therapy and sometimes immunosuppressive treatment is necessary in the case of corticosteroid unresponsiveness.